MANAJEMEN PENDIDIK DAN TENAGA KEPENDIDIKAN DI MADRASAH TSANAWIYAH DARUL IMAN KECAMATAN SINGKEP KABUPATEN LINGGA PROVINSI KEPULAUAN RIAU - Muliadi; Umi Kulsum; Riskun Iqbal; Suci Hartati (UNISAN JURNAL, 2022)
This research uses qualitative research with case study design. Data and documents were collected and compiled using in-depth interview techniques, participant observation and documentation studies. The data and documents were checked for validity through triangulation of methods, theories and sources. Furthermore, the data and documents were analyzed descriptively qualitatively. The purpose of this study was to compare human resource management for educators and education staff in Madrasahs. Aspects of the comparison include, comparison of the management of Educator Recruitment Planning, Organizing the Placement of Educators and Educational Staff, Mobilizing Educators and Educational Personnel, and Management The most important subjects in this study are the head of madrasah, teachers, madrasa committees from the two schools, have many similarities and differences. differences in several aspects are therefore mandatory to improve the quality of madrasas and are expected to become treasures and inputs for madrasas. The results of the analysis are stated in the main tasks and functions, the results of this job analysis are carried out filling and placing personnel in positions according to intellectual capacity, capability, work experience and exemplary. (1) the withdrawal and selection of GTT and PTT candidates is carried out based on considerations of academic achievement, non-academic, and good character. (2) the training and development of human resources carried out still tends to measure the success and failure of training in terms of implementation, not oriented to whether the training carried out is effectively able to change the behavior and performance of the participants towards the goals of the madrasa. (3) evaluation is carried out using three stages, namely monthly evaluation, mid-semester and year-end evaluation. The main duties and functions as a standard of work, become a benchmark or a tool for assessing the level of success and failure of an educator and education staff, in this case the Principal as a supervisor who is assisted by several appointed people. Keywords: Educator management, Education staff